Pemberdayaan Ibu Rumah Tangga melalui Pelatihan Pengelolaan Keuangan Keluarga di Kelurahan Tampa Garam Kota Sorong Papua Barat Daya - Bintari, Wisang Candra; Amin, Muhammad; Waly, Nur Aeni; Wangsi, Mitta Muthia; Lestari, Bekti Wiji; Nurhani, Nurhani; Howay, Korintus; Kambu, John Regen (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service activity was carried out with the aim of enhancing the ability of housewives to manage family finances effectively and wisely in Tampa Garam Village, Sorong City, Southwest Papua Province. The low level of financial literacy among housewives in this area has become the main issue, resulting in limited skills in financial planning, recording expenses, and determining family financial priorities. To address these problems, the training program was designed through four stages: socialization and interactive discussion, core material training, assistance in budget preparation, and evaluation through group discussions. A total of 23 participants took part in this activity and gained comprehensive understanding of the five key steps in family financial management, which include budgeting, determining expenditure priorities, managing debt responsibly, developing saving and investing habits, and monitoring and evaluating family financial conditions regularly. The results of the training indicate a significant improvement in participants’ knowledge and skills, especially in creating more structured financial plans based on household needs. Participants were able to prepare clearer family budgets, set expenditure priorities wisely, and understand the risks associated with poor debt management. Additionally, they demonstrated increased awareness of the importance of saving and investing as a means of anticipating unexpected financial needs in the future. Overall, this activity successfully achieved its objective by providing tangible benefits for improving family financial literacy and encouraging participants to become more independent in managing household financial matters.